Screening for Cushing’s Syndrome: New Immunoassays Require Adequate Normative Data - Deutschbein, T.; Petersenn, S. (Hormone and Metabolic Research, 2013)
Cushing’s syndrome results from chronic inappropriate exposure to excessive glucocorticoid concentrations. Low-dose dexamethasone suppression, late-night salivary cortisol, and 24-h urinary free cortisol are regarded as screening tests of first choice. Consequently, measurement of circulating cortisol (e. g., in serum, saliva, and urine) is mandatory in the diagnostic workup of suspected patients. The particular analytical procedure needs to be chosen carefully. Antibody-based immunoassays offer several potential advantages: they require small volumes and are widely available, relatively cheap, and easy to handle. Modern (ideally automated) systems also have a rapid turnaround time on a large number of samples and demonstrate high analytical accuracy. However, there are some important pitfalls. Inadequate standardization and poor interlaboratory performance remain problematic and precise reference ranges are lacking for some of the newer assays. Immunoassays are also susceptible to error due to cross-reactivity with cortisol metabolites or exogenous glucocorticoids. In contrast, steroid analysis by modern chromatographic and mass spectrometric techniques is largely independent from such interference and is therefore regarded as diagnostic gold standard. To date, however, these procedures are costly, time-consuming, and at least at present restricted to a limited number of specialized centers. This review puts special emphasis on the potential advantages of salivary cortisol analysis by immunoassays. It has been shown in numerous studies that such an approach allows excellent identification of hypercortisolemic states. In this context, use of automated systems may allow for broader use of this diagnostic tool.
Keywords: cortisol; Cushing’s disease; glucocorticoids; hypercortisolism; measurement; reference range